Creating space for Indigenous healing practices in patient care plans - Logan, Lindsey; McNairn, Jacinta; Wiart, Shelley; Crowshoe, Lynden; Henderson, Rita; Barnabe, Cheryl (Canadian Medical Education Journal, 2020)
Background: The Truth and Reconciliation Commission of Canada’s Calls to Action ask that those who can effect change within the Canadian healthcare system recognize the value of Indigenous healing practices and support them in the treatment of Indigenous patients. Methods: We distributed a survey to the Canadian Rheumatology Association membership to assess awareness of Indigenous healing practices, and attitudes informing their acceptance in patient care plans. Results: We received responses from 77/514 members (15%), with most (73%) being unclear or unaware of what Indigenous healing practices were. Nearly all (93%) expressed interest in the concept of creating space for Indigenous healing practices in rheumatology care plans. The majority of support was for the use in preventive or symptom management strategies, and less as adjuncts to disease activity control. Themes identified through qualitative analysis of free-text responses included a desire for patient-centered care and support for reconciliation in medicine, but with a colonial construct of medicine, demonstration of an evidence bias, and hierarchy of medicines. Conclusions: Overall, respondents were open to the idea of inclusion of Indigenous healing practices in patient’s car plans, emphasizing importance for patient empowerment and patient-centered care. However, they cited concerns that provide the indication for further learning and reconciliation in medicine.